Changes in biomass and essential oil profile of four Lamiaceae species due to different soil water levels. Issue 5 (2nd September 2016) - Németh-Zámbori, Éva; Szabó, Krisztina; Pluhár, Zsuzsanna; Radácsi, Péter; Inotai, Katalin
Abstract: The reactions of Majorana hortensis, Melissa officinalis, Mentha piperita and Thymus vulgaris were investigated in controlled conditions to compare their responses on drought stress concerning yield, essential oil (EO) content and composition. Biomass and essential oil concentration were significantly decreased in each species similarly, if they were grown at 40% level of soil water capacity (SWC) compared to the ones growing at 70% SWC. The largest changes were detected in lemon balm (4.47-fold difference in biomass, 2.78-fold difference in EO content) while the response of marjoram was the modest one (1.95-fold in biomass, 1.21-fold in EO content). We found species specific quantitative modifications in the EO composition. The ratio of terpinene-type components increased in the EO of both thyme and marjoram to the expense of their characteristic compounds thymol, carvacrol and sabinyl compounds, respectively. The composition of lemon balm and peppermint, however, did not show considerable changes.